The Role of Coenzyme Q10 in Energy Metabolism and Cell Stability: A Critical Review Based on a Systematic Literature Review - Nur Saropah Lubis; Sarah Khairani; Miftahul Khairani; Dewi Kartika Br Ginting; Nicky Salsa Dalila (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2026)
This study aims to examine the role of coenzyme Q10 (CoQ10) in energy metabolism and cell stability through a Systematic Literature Review (SLR) approach. Coenzyme Q10 is an essential component in the electron transport chain in mitochondria that plays a role in the production of adenosine triphosphate (ATP) as the main energy source of cells. In addition, CoQ10 also has antioxidant activity that can protect cells from damage due to oxidative stress. The method used in this study is SLR by analyzing two relevant scientific articles, namely those discussing the physiological and pharmaceutical aspects of CoQ10. The results of the study indicate that CoQ10 has a dual role, namely as an energy producer and cell protector. In the pharmaceutical context, the use of a liposome-based delivery system has been shown to increase the stability and bioavailability of CoQ10. A critical analysis of both articles shows that the integration of biological approaches and pharmaceutical technology is crucial to optimize the benefits of CoQ10. Thus, this study provides a comprehensive understanding of the importance of coenzyme Q10 in life and its potential in the development of coenzyme-based therapies in the health sector.